1972
DOI: 10.1017/s0022112072002514
|View full text |Cite
|
Sign up to set email alerts
|

Flow visualization of the near-wall region in a drag-reducing channel flow

Abstract: The objectives of this study were to determine whether the addition of drag-reducing macromolecules alters the structure of the viscous sublayer and thereby modifies the production of kinetic energy in turbulent wall flows. This was accomplished by visualizing the near-wall region of a fully developed two-dimensional channel flow. Motion pictures were taken of dye injected into the near-wall region. Both water and a dilute drag-reducing polyethylene oxide-FRA solution were used as working fluids. The motion pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
65
0

Year Published

1975
1975
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(70 citation statements)
references
References 20 publications
(14 reference statements)
5
65
0
Order By: Relevance
“…Observations of drag-reducing fluids indicate that, at least near the onset Reynolds number for drag reduction, the effects of the polymer are confined primarily to the near-wall buffer layer, 1,[5][6][7][8] which is the most important region for the production and dissipation of turbulent energy. 9 From experia)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations of drag-reducing fluids indicate that, at least near the onset Reynolds number for drag reduction, the effects of the polymer are confined primarily to the near-wall buffer layer, 1,[5][6][7][8] which is the most important region for the production and dissipation of turbulent energy. 9 From experia)…”
Section: Introductionmentioning
confidence: 99%
“…Most notably, the wall-normal thickness of the buffer region increases, 1 the coherent structures in this region shift to larger length scales, 5,[12][13][14] and the bursting rate decreases. 5 These structural changes are accompanied by changes in the root-mean-square (rms) velocity fluctuations and Reynolds stresses. Namely, the wall-normal and spanwise fluctuations are reduced while, at least at low to moderate degrees of drag reduction, the streamwise velocity fluctuations are enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…The changes in the burst events in drag-reducing flows are particularly interesting because the variations of velocity field in the near-wall region during a burst could reveal the mechanism of DR and could also exhibit the basic relationship of turbulent structures. Donohue et al 22 examined the effects of polymers on turbulent structures by using the visualization technique; they reported that the streaking spacing and bursting rates in drag-reducing flow are different from that in the Newtonian flow, i.e., the average nondimensional spacing between streaks linearly increases with increasing DR and the viscous sublayer was more stable when polymer solutions were present. A suppression of the burst process and an increment of streak spacing were also reported by Berman 16 and Tiederman et al 23 However, Luchik and Tiederman 19 found that the method for deducing the time between bursts was not accurate in these experiments because they did not marked and counted all of these events.…”
Section: Introductionmentioning
confidence: 99%
“…The central rheological feature of drag-reducing additives is their extensional behavior in solution: for dilute polymer solutions in particular the stresses arising in extensional flow can be orders of magnitude larger than those developed in a shear flow. This fact is well-recognized; nevertheless the mechanism of interaction between polymer stretching and turbulent structure is not well-understood and the goal of the present work is to attempt to shed light on this interaction.A key structural observation from experiments and direct numerical simulations (DNS) of drag-reducing solutions is the modification of the buffer region near the wall [4,5,6,7,8,9,10]. It has long been known that the flow in this region is very structured, containing streamwise vortices that lead to streaks in the streamwise velocity [11]; these structures are thickened in both the wall-normal and spanwise directions during flow of drag reducing solutions [4,5].…”
mentioning
confidence: 99%
“…It has long been known that the flow in this region is very structured, containing streamwise vortices that lead to streaks in the streamwise velocity [11]; these structures are thickened in both the wall-normal and spanwise directions during flow of drag reducing solutions [4,5]. Because of its importance in the production and dissipation of turbulent energy [11], any effort to mechanistically understand rheological drag reduction should address this region.…”
mentioning
confidence: 99%